Germany : Financial Sector Assessment Program-Crisis Preparedness, Bank Resolution and Crisis Management Frameworks-Technical Notes. (IMF Staff Country Reports; Country Report ;, 2016)
This paper analyzes the crisis preparedness and crisis management frameworks for German banks. Banks dominate German financial system and represent one of the largest small- and medium-sized banking segments in the EU. The banking sector is a three-pillar system with a total of nearly 1,800 institutions. Both at the EU level and at domestic German level a range of legal instruments have been adopted that collectively establish a complex framework for bank resolution and crisis preparedness and management in financial sector. The Single Supervisory Mechanism Regulation has conferred specific tasks on the European Central Bank concerning prudential supervision of banks including the adoption of early intervention measures and a requirement that banks prepare recovery plans.